Evaluasi Penerapan Prinsip Manajemen Sumber Daya Manusia Islam (MSDI) dalam Meningkatkan Kinerja Karyawan di Polres Tapin Polda Kalimantan Selatan - Dody Irianto; Zakky Zamrudi; Syahrial Shaddiq (PT. Saha Kreasi Indonesia, 2025)
Human resource management (HRM) is crucial for any organization, enabling it to achieve work effectiveness and efficiency. Islamic Human Resource Management (HRM) is an alternative human resource management approach that emphasizes professionalism alongside spirituality and morality. The Tapin Police Department, as an agency with significant responsibilities for the territory of the Republic of Indonesia (NKRI), requires human resources who are technically and professionally competent, possessing strong moral and spiritual qualities. However, several challenges remain in integrating HRM principles into the existing management system. Therefore, the author aims to evaluate the extent to which the implementation of HRM principles at the Tapin Police Department contributes to improving personnel performance. This study employed a descriptive qualitative research method, an approach that focuses in-depth on the natural conditions of the object, namely the implementation of HRM within the Tapin Police Department, with the researcher as the key instrument. Data collection used triangulation, a combined method. Data were collected through observation, interviews, and documentation. The research results indicate that the implementation of MSDI principles such as trustworthiness, justice, ihsan, and deliberation has been integrated into human resource management practices at the Tapin Police, although not yet fully optimal. Supporting factors for MSDI implementation include religious leadership and a family-like organizational culture, while inhibiting factors are the lack of training and a deep understanding of MSDI values. Overall, the implementation of Islamic values has been shown to have a positive effect on increasing employee motivation, discipline, and performance.